Pengembangan Buku Ajar Berbasis HOTS Dimensi Taksonomi Bloom Tema 8 Subtema 1 Kelas 4 - Wahyuni Mariana; Benny Angga Permadi (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The research aimed to compile HOTS textbooks based on Bloom's Taxonomy dimensions for grade 4 students at MI Dwi Dasa Warsa. The development of this book is limited to thematic subjects, namely the theme of 8 sub-themes 1 class 4. This research is a Research and Development research with a 4-D development model approach to the Thiagarajan Model which has 4 stages, namely Define, Design, and Develop ( Development) and Disseminate (Spread). This textbook was validated by 2 material experts (subject matter expert lecturers and subject teachers), 1 media expert and 24 students who were the research objects. Textbooks were tested on 24 grade 4 students of MI Dwi Dasa Warsa. Data collection used interview techniques to subject teachers and grade 4 students. The results showed that this textbook as a whole was suitable for use as teaching materials. This is indicated by the results of the validation by the material expert lecturer with a total score (X) greater than the total comparison score (138> 104.95) and is included in the category A value (very good) and the validation results by the subject teacher with a total score ( X) is greater than the total comparison score (167> 104.95) and is in the category A score or very good. Meanwhile, the results of the validation by media experts got a total score (X) greater than the total comparison score (106> 72) which was categorized as A or very good. Validation by students with the calculation of SPSS Person Correlation shows that all scores have reached more than 0.05 and can be said to be valid